Customer Value and Competitive Advantage in Schools at Cirebon - Suklani, Suklani; Sibaweh, Imam (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to determine the customer value and competitive advantage of schools in Cirebon. Customer value provides customer response with competitive advantages and competition in education by increasing educational competitiveness. Research method with qualitative approach using description analysis. This method is used because Cirebon has 45 high school schools with a sample of 20 varied schools. Data collection techniques use interviews, documentation, and observation. The research results were analyzed using data triangulation techniques. The result of the study is that customer value requires the readiness of all parties involved in the school, and customer value requires commitment from every member of the school element. Competitive advantage requires the carrying capacity of school principals and the smart work of all parties who can manage Education programs.